Keeping the Landscape Running - Kędziora, Andrzej; Ryszkowski, Lech (ACADEMIA. The magazine of the Polish Academy of Sciences, 2004)
Shelterbelts and forested patches surrounding cultivated fields are far more than just an aesthetic component of the rural landscape. They have an impact on vital cycles of matter and energy.